Synthesis of Nanocomposite Based on Poly Methylene-imidazole as Effective Catalyst in Oxidation of Some Hydrocarbones - Abdul-Redhah Aidan, Muhanned; Mahdi Alkoofee, Wafaa; A. Sultan, Ala`a; M. Khamis, Wessal; Medhat, Sinan (International Journal of Engineering and Technology, 2018)
The polymers derived from heterocyclic rings like imidazole was prepared and supported to produce catalytic active supported catalyst. This catalyst was characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), H NMR and UV-visible spectroscopy. The catalyst showed high catalytic activity in the oxidation of cyclohexene and cyclopentene under optimized conditions. In this work cyclohexene and cyclopentene were selected as model alkene for determination the capacity of the prepared imidazole polymer catalyst under optimized conditions of temperature and time of reaction. The catalyst could be readily separated from the catalytic system using uploading 3-5 milligrams of Copper(II), Nickel(II) and Cobalte(II) ions with the surface of polymer the conversion them to nano-particle which are identified by x-ray diffraction. For this research, a statistical method called Response Surface Methodology (RSM) has been used to economize the number of experiments and their meaningful interpretation. The effect of metallated polymer with Copper(II), Nickel(II) and Cobalte(II) were taken to increase the efficiency of oxidation. Optimization results for 0.33 mmole cyclohexene and cyclopentene showed that maximum oxidation efficiency 90. % was achieved at the optimum conditions: catalyst amount 350 mg, temperature 70.0, time 3.30 h and oxidant= 5.25 m mole.Â Â Â